METODE INKUIRI PADA PEMBELAJARAN IPA DISEKOLAH DASAR NEGERI X - -, Syamsuarni (Universitas Negeri Padang, 2014)
ABSTRACT This class action research aimed at improving student’s natural science learning outcomes by using the inquiry method at the sixth grade of SDN X. The subjects of the research were twenty four sixth grade students. The data analysis showed that: a) the result of the lesson plan analysis increased from 80,35% in cycle I to 92,85 in cycle II, b) the result of the teachers’ activities analysis increased from 79,68% in cycle I to 93,75% in cycle II.Meanwhile, the result of the students’ activities analysis increased from 76,56% in cycle I to 90,62% in cycle II, and c) the learning outcome increased from 73,93% in cycle I to 84,63% in cycle II. Thus, the inquiry method successfully improved the sixth grade students’ natural science learning outcomes at SDN X. Kata Kunci: hasil belajar, siswa,IPA, inkuiri